The Relationship between School Happiness and Digital Game Addiction - Semih Cayak; Ozge Erduran-Tekin (Journal of Education in Science, Environment and Health)
The purpose of this research is to examine the relationship between primary school students' school happiness and digital game addictions. The study group of this research, which was designed in the relational survey model, consists of 204 fourth-grade primary school students studying in the Pendik district of Istanbul. In the research, the “School Happiness Scale for Primary School Children” developed by Ozdemir et al. (2021) and “The Digital Game Addiction Scale” which was developed by Lemmens, Valkenburg & Peter (2009) and adapted into Turkish by Yalçın-Irmak & Erdoğan (2015), and later whose validity and reliability analyzes were made for primary school children by Oral and Arabacıoglu (2019) were used. According to the research findings, it was found that the students' school happiness was at a moderate level and their digital game addiction was at a high level. Students' school happiness levels and digital game addiction levels do not show significant differences according to their genders. Similarly, the digital game addiction levels of students do not differ statistically according to the gender of their teachers, but the school happiness levels of students with female teachers are statistically significantly higher than those with male teachers. On the other hand, while the digital game addiction levels of the students do not differ significantly according to the school success of the students, the school happiness levels of the students with medium school success are significantly higher than the students with low or very high school success. According to another finding obtained from the research, there is a negative, low, and significant relationship between students' school happiness levels and digital game addiction levels. As a result of the regression analysis, it was seen that school happiness was a significant predictor of digital game addiction. School happiness explains 3% of digital game addiction.